NATIONAL ENGINEERING INDUSTRIES LTD. - A CASE STUDY ISSUES, ASPECTS AND STEPS INVOLVED IN MARKETING BEARINGS INTERNATIONALLY - Taparia, Sunayna (2008)
With the globalization of the world economies, International Marketing is gaining more and more prominence. India being a developing economy has recently entered into the global market. It will be very interesting and challenging to take up International Marketing of bearings, of an Indian company. I choose National Engineering Industries Ltd. To conduct my research, as it is a leading bearing company in India and also because it is in the process of making a strong hold internationally which would give me an opportunity to explore all avenue available to them.